Structural studies of the brass ingots from the Shcherbet historical complex of the Lower Kama region: neutron diffraction and tomography studies - Zhomartova, A; Shaykhutdinova, E.F.; Bakirov, B.A.; Kichanov, S.E.; Kozlenko, D.P.; A.G. Sitdikov, A.G. Sitdikov (Eurasian Journal of Physics and Functional Materials, 2026)
The structural characteristics and phase composition of several ancient brass ingots obtained in the archeological Shcherbet complex has been studied using neutron diffraction and tomography methods. The XRF analysis and neutron diffraction provide high zinc content up to 30 wt.%. The neutron tomography yielded 3D data of the spatial distribution of chemical elements in the brass alloy of the studied ingots, as well as inner voids and cavities as a possible result of the gas output during casting process. The patina, as a cuprite phase, occupy volumes to 8 % of the volumes of the ingots. © 2022, Eurasian Journal of Physics and Functional Materials. All Rights Reserved.Recommended CitationZhomartova, A. Zh.; Shaykhutdinova, E. F.; Bakirov, B. A.; Kichanov, S. E.; Kozlenko, D. P.; and Sitdikov, A. G. (2022) "Structural studies of the brass ingots from the Shcherbet historical complex of the Lower Kama region: neutron diffraction and tomography studies," Eurasian Journal of Physics and Functional Materials: Vol. 6: No. 3, Article 3.DOI: https://doi.org/10.32523/ejpfm.2022060303